2022
DOI: 10.1002/sce.21702
|View full text |Cite
|
Sign up to set email alerts
|

Emotion, place, and practice: Exploring the interplay in children's engagement in ecologists' sampling practices

Abstract: In science education, there has been a sustained focus on supporting the emergence of science practices in K–12 and field‐based settings. Recent work has elevated the integral role of emotion in sparking and sustaining such disciplinary practices, deepening the field's understanding of what is entailed in “doing” science. Yet even as we gain this richer understanding of practice, less attention has been given to the places where practice emerges. These places play a critical role in the co‐emergence of emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…To explore an expansive view of feelings in science classrooms, Lanouette (2022) used the lens of emotional configurations (Vea, 2020) to analyze elementary students' participation in ecological sampling, attending to students' feelings, not only toward disciplinary activity but also toward their peers and the places in which their work took place. In this study, Lanouette aimed to resist “depictions of science practice as purely cognitive and decontextualized” (p. 612) by drawing on the work of philosophers of science and science education researchers who have taken holistic and justice‐oriented stances toward science and science education.…”
Section: Literature Review: Feelings Sensemaking and Practices In Sci...mentioning
confidence: 99%
See 1 more Smart Citation
“…To explore an expansive view of feelings in science classrooms, Lanouette (2022) used the lens of emotional configurations (Vea, 2020) to analyze elementary students' participation in ecological sampling, attending to students' feelings, not only toward disciplinary activity but also toward their peers and the places in which their work took place. In this study, Lanouette aimed to resist “depictions of science practice as purely cognitive and decontextualized” (p. 612) by drawing on the work of philosophers of science and science education researchers who have taken holistic and justice‐oriented stances toward science and science education.…”
Section: Literature Review: Feelings Sensemaking and Practices In Sci...mentioning
confidence: 99%
“…Attending to emotion in this way takes students' feelings and their role in investigations seriously. Yet, education research that attends to emotion as a part of science, rather than as ancillary to disciplinary engagement, is relatively nascent (e.g., Jaber & Hammer, 2016b; Lanouette, 2022). As a result, the role of emotion in learning is undertheorized (Boler, 1999).…”
mentioning
confidence: 99%
“…For example, by considering students' sustained engagement, social interactions around the model (e.g., spontaneous agreeing and disagreeing), and students bringing target concepts to bear on their modeling and social work (Manz, 2012, 2015). In these cases, the energy and drive for modeling comes from students pushing ideas along, rather than teachers “doing all of the work.” Other work has begun to ask young people whether they understand why they are doing what they are doing in class and what their experience of classroom activity is (Raza et al, 2021; Zivic et al, 2018) and attending to the role of emotion in students' activity (e.g., Lanouette, 2022). Such indicators need to be at the center of efforts in promoting and evaluating modeling—rather than at the periphery.…”
Section: Promising Directions For Modelingmentioning
confidence: 99%
“…For example, Soini et al (2012) believed that sense of place is closely related to the experience of place. Other scholars argue that sense of place and emotion are inseparable ( Lanouette, 2022 ). It has also been shown that urban environmental education is important in developing a sense of place among young people which can make them aware of the ecological value of urban landscapes and thus further promoting awareness of the benefits of protecting and managing the natural environment in cities ( Kudryavtsev et al, 2012 ).…”
Section: Theoretical Basis and Hypothesismentioning
confidence: 99%